Insulin-like peptide 5 is a microbially regulated peptide that promotes hepatic glucose production - Ying Shiuan Lee; Filipe De Vadder; Valentina Tremaroli; Anita Wichmann; Gilles Mithieux; Fredrik Bäckhed (Elsevier, 2016)
Objective: Insulin-like peptide 5 (INSL5) is a recently identified gut hormone that is produced predominantly by L-cells in the colon, but its function is unclear. We have previously shown that colonic expression of the gene for the L-cell hormone GLP-1 is high in mice that lack a microbiota and thus have energy-deprived colonocytes. Our aim was to investigate if energy deficiency also affected colonic Insl5 expression and to identify a potential role of INSL5. Methods: We analyzed colonic Insl5 expression in germ-free (GF), conventionally raised (CONV-R), conventionalized (CONV-D) and antibiotic-treated mice, and also assessed the effect of dietary changes on colonic Insl5 expression. In addition, we characterized the metabolic phenotype of Insl5−/− mice. Results: We showed that colonic Insl5 expression was higher in GF and antibiotic-treated mice than in CONV-R mice, whereas Insl5 expression in the brain was higher in CONV-R versus GF mice. We also observed that colonic Insl5 expression was suppressed by increasing the energy supply in GF mice by colonization or high-fat feeding. We did not observe any differences in food intake, gut transit or oral glucose tolerance between Insl5−/− and wild-type mice. However, we showed impaired intraperitoneal glucose tolerance in Insl5−/− mice. We also observed improved insulin tolerance and reduced hepatic glucose production in Insl5−/− mice. Conclusions: We have shown that colonic Insl5 expression is regulated by the gut microbiota and energy availability. We propose that INSL5 is a hormone that could play a role in promoting hepatic glucose production during periods of energy deprivation. Keywords: Insulin-like peptide 5 (INSL5), Gut microbiota, Liver, Colon